Influence of an SGLT2 inhibitor, tofogliflozin, on the resting heart rate in relation to adipose tissue insulin resistance. Issue 8 (17th March 2020) - Nojima, T.; Matsubayashi, Y.; Yoshida, A.; Suganami, H.; Abe, T.; Ishizawa, M.; Fujihara, K.; Tanaka, S.; Kaku, K.; Sone, H.
Abstract: Aims: To examine the effects of a sodium–glucose co‐transporter 2 (SGLT2) inhibitor, tofogliflozin, on resting heart rate by exploring baseline factors that independently influenced changes in the resting heart rate. Methods: Data on 419 participants in tofogliflozin phase 2/3 trials were analysed. Changes in resting heart rate from baseline to week 24 were analysed using an analysis of covariance (ANCOVA) model with groups (tofogliflozin/placebo) as a fixed effect and baseline values as covariates. The antilipolytic effect was evaluated as adipose tissue insulin resistance (Adipo‐IR) and was calculated as the product of fasting insulin and free fatty acid. Multivariate analysis evaluated independent factors for changes in resting heart rate from baseline to week 24. Results: Of the participants, 58% were men, and mean age, HbA1c, BMI and resting heart rate were 57.6 years, 65 mmol/mol (8.1%), 25.5 kg/m 2 and 66 bpm, respectively. At week 24, adjusted mean difference vs. placebo in the change from baseline was −2.3 bpm [95% confidence interval (CI) −4.6, −0.1] with tofogliflozin. Changes in resting heart rate were positively correlated with changes in Adipo‐IR, whereas reductions in HbA1c, body weight and blood pressure were similar independent of changes in resting heart among quartiles of resting heart rate change. On multivariate analysis, higher baseline resting heart rates and Adipo‐IR values were significantly associated with greater reductions in resting heart rate. Conclusions: Tofogliflozin corrected resting heart rate levels in accordance with baseline levels. Correction of high resting heart rates may be attributed to improved adipose tissue insulin resistance, leading to correction of hyperinsulinaemia. What's new?: A high resting heart rate is related to increased cardiovascular and microvascular risks in persons with type 2 diabetes. Tofogliflozin significantly reduced resting heart rate compared with placebo, irrespective of reductions in HbA1c, body weight and blood pressure. Reduction in resting heart rate was associated with improvements in adipose tissue insulin resistance. Higher baseline adipose tissue insulin resistance levels were independently associated with a greater decline in resting heart rate. Correcting the resting heart rate via improved adipose tissue insulin resistance by tofogliflozin treatment might contribute to lowering the risks of cardiovascular diseases.